2023
DOI: 10.7822/omuefd.1286835
|View full text |Cite
|
Sign up to set email alerts
|

Taking Interdisciplinary Science Learning to Nature

Bekir GÜLER,
İsmail EYÜPOĞLU,
Fatih TAŞ
et al.

Abstract: In recent years, efforts to form a sustainable community rather than a consumption society deprived of nature have accelerated. To raise this awareness in individuals and; more importantly, to make it sustainable, education plays a significant role. Informal and nonformal learning are vital resources for individuals to recognize the importance of nature and to establish a healthy and balanced relationship with science and nature. One of the settings to experience such learning is science and nature camps. In l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This study points out a more comprehensive interrelation among subjects. A study about taking interdisciplinary science learning to nature revealed that students as they immerse themselves in nature, develop an understanding of the role of science and their place as individuals in the natural world (Güler et al, 2023). Like the interplay between mathematics and language, we appreciate science from a different perspective if we view ourselves as part of it.…”
Section: Interesting Discoveries With the Teaching Experiencementioning
confidence: 99%
“…This study points out a more comprehensive interrelation among subjects. A study about taking interdisciplinary science learning to nature revealed that students as they immerse themselves in nature, develop an understanding of the role of science and their place as individuals in the natural world (Güler et al, 2023). Like the interplay between mathematics and language, we appreciate science from a different perspective if we view ourselves as part of it.…”
Section: Interesting Discoveries With the Teaching Experiencementioning
confidence: 99%